2022
DOI: 10.1128/spectrum.00814-22
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and Functional Shifts in the Perinatal Gut Microbiome of Rhesus Macaques

Abstract: Pregnancy and the postpartum period are characterized by a myriad of metabolic and physiological adaptations needed to support fetal growth and maternal health. The maternal gut microbiome is believed to play a key role during this period but remains underexplored.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
1
0
0
Order By: Relevance
“…We also found that the gut microbiome of dams that gave birth to infants who experienced diarrhea was both functionally and taxonomically distinct prior to the infants becoming sick, including increased pathogen burden (Campylobacter jejuni and Escherichia coli). Our data align with recent ndings from human cohorts that demonstrated that the maternal microbiome can modulate the infant microbiome composition, immune development, and infant growth [52][53][54] . However, the mechanism by which the maternal microbiome in uences protection and/or vulnerability to disease in the infant deserves further attention as the maternal microbiome is dynamic during the perinatal period.…”
Section: Disscusionsupporting
confidence: 91%
“…We also found that the gut microbiome of dams that gave birth to infants who experienced diarrhea was both functionally and taxonomically distinct prior to the infants becoming sick, including increased pathogen burden (Campylobacter jejuni and Escherichia coli). Our data align with recent ndings from human cohorts that demonstrated that the maternal microbiome can modulate the infant microbiome composition, immune development, and infant growth [52][53][54] . However, the mechanism by which the maternal microbiome in uences protection and/or vulnerability to disease in the infant deserves further attention as the maternal microbiome is dynamic during the perinatal period.…”
Section: Disscusionsupporting
confidence: 91%